Implementation of Zoo Management Strategies for Animal Welfare in Indonesia - Arba, Risqi Mutia; Novarino, Wilson; Rizaldi, Rizaldi (Al-Hayat: Journal of Biology and Applied Biology, 2023)
A zoo is a place to live or collect wild animals outside their natural habitat which can be controlled by the government or non-government, and functions as a breeding ground so that natural genetics is maintained. Apart from being a place of conservation, it is also a place of education and a place of recreation. The problem with zoos in Indonesia is that their management is not by the principles of animal welfare. This study aims to summarize the results of the Systematic Literature Review (SLR) by collecting reference articles related to the keyword "Implementation of Zoo Management Strategies based on Animal Welfare Standards". Management efforts must pay attention to the survival of animals by the principles of animal welfare, namely freedom from hunger and thirst; free from pain, injury, and disease; free from environmental discomfort, abuse, and violence; freedom from fear and depression; and free in expressing natural behavior. Pay attention to zoo management, both animals and officers or keepers according to their expertise. Strategy implementation using SWOT analysis, namely analysis that obtains useful strategies to implement or recommendations based on results that can maximize Strengths and Opportunities, by minimizing Weaknesses and avoiding Threats.